Wage inequality, linkages and FDI - Nigel Driffield; Sourafel Girma; Michael Henry; Karl Taylor (Institute for the Study of Labor (IZA), 2010)
This paper extends the existing literature on FDI and wage inequality. We do this in two ways. Firstly, we incorporate more precise measures of inward investment into the model, by allowing for differences in the effects between horizontal and vertical FDI. Secondly, after establishing the effects that inward investment has on wage inequality, we then analyse the reasons for this in terms of the wages paid to skilled and unskilled workers, and the effect that inward investment has on this. We illustrate the important differences that horizontal and vertical FDI have on both wages and wage inequality, and the importance of allowing for regional differences in the results. FDI nationally tends to increase wage inequality, while the local, effects are opposite. FDI into assisted areas tends to increase wage inequality nationally, when the MNEs purchase inputs in the local region.
Keywords: F21; F23; J31; 330; Wage inequality; FDI spillovers; backwards and forwards linkages; Lohnstruktur; Direktinvestition; Ausländisch; Qualifikation; Schätzung; Großbritannien